Teknik Komunikasi Human Relations Mentari Cilik Indonesia dalam Membangun Perilaku Komunikasi Islami Anak Muslim di Desa Rumamis Kecamatan Barusjahe Kabupaten Karo - Nasution, Najiyah Maisaro Br; Kholil, Syukur (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Communication techniques are important in communicating as a process of conveying messages, ideas and concepts. By communicating with someone directly we can understand how behavior is especially seen in children. Communication that exists is not only found in the family environment, but activities in the community also have an impact on the communication techniques used to develop behavior in children. In this case, Mentari Little Indonesia, in activities that take place in the community, applies communication techniques, especially to children, to form good behavior in communicating with the environment, family and also society. With this research, it is explained that children's activities that take place within the scope of the Mentari Little Indonesia community apply appropriate communication techniques to children, paying special attention to children's behavior that is far from Islamic communication behavior so that it is more regularly directed and in accordance with Islamic guidance as an Islamic generation.